New control strategy for East Coast Fever - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Infecting calves with Theileriosis which causes East Coast Fever, and then immediately treating them is the latest strategy to beat this major disease of cattle in Africa. This strategy appears to give the cattle immunity for life. East Coast Fever...